Hard-to-Reach Areas : Providing Water Supply and Sanitation Services to All - Ahmed, Rokeya (World Bank, Washington, DC, 2014)
Water Sanitation coverage in Bangladesh has significantly improved in the last couple of years but research outputs or reports and experience of water and sanitation (WatSan) service providers suggest that there exist pockets of areas in Bangladesh where WatSan services are not adequate by any standard. Based on practical experience, many of those areas have been identified and termed Hard to reach Areas (HtRAs), which creates the notion that WatSan service providers fail to reach or find it difficult to provide services to these specific areas, however in Banglades, HtRAs can be conceptualized and understood from wider perspectives. For practical purposes, HtRAs are defined in Bangladesh in terms of both their remote geographical location as well as population residing out of the range of development activities. This leads to consideration of issues covered in a socioeconomic factorial analysis, that is, cultural diversity, religious norms, traditional practices, and social norms and values, which play a crucial role in water and sanitation coverage as well as behavioral change in Bangladesh. The community composition, ethnicity, geo-physical traits and environment are determinant factors in achieving success in water and sanitation coverage and behavioral change.